DEMS and in-situ FTIR investigations of C3 primary alcohols on platinum electrodes in acid solutions : Part II. Allyl alcohol - Pastor, E. (1993)
On-line mass spectroscopy (DEMS) and in-situ Fourier transform IR spectroscope (FTIRS) have been employed to study the electro-oxidation and the electroreduction products of allyl alcohol on Pt electrodes in acids. The electroreduction products were propanol and a mixture of propylene, propane and ethane. The main oxidation products were CO2 and acrolein. Results are interpreted and possible mechanisms are suggested with the participation of adsorbates having different chain lengths and structures.